(untitled) (Research, Society and Development, 2021)
The Brazilian nursery has been fighting for professional recognition, a more humane workload and a fairer salary policy. In this context, mid-level nursing professionals are also included. The objective of this study was to analyze a time series of salaries of nursing assistants and technicians in their first job, from 2010 to 2019. A retrospective epidemiological study was carried out with graduates of a nursing technician course from the federal education network from 2010 to 2019. The 143 graduates were included, most of them young women. The average remuneration was R1,702.92 (minimum of R790.00 and maximum of R4,000.00). The wage time series is a constant trend in the period analyzed, while the minimum wage has an increasing trend. The remuneration of nursing technicians/auxiliaries is below what the professional category wants. The existence of a bill that determines the category’s wage floor and a working day is in line with the valuation of working workers; and its implementation as a public policy tends to strengthen this collective. The salary stagnation evidenced in the time series may represent a risk of professional evasion for other types of work.